Host genetic backgrounds: the key to determining parasite-host adaptation - Ye, Caixia; Zhang, Lianhua; Tang, Lili; Duan, Yongjun; Liu, Ji; Zhou, Hongli (Frontiers in Cellular and Infection Microbiology, 2023)
Parasitic diseases pose a significant threat to global public health, particularly in developing countries. Host genetic factors play a crucial role in determining susceptibility and resistance to infection. Recent advances in molecular and biological technologies have enabled significant breakthroughs in understanding the impact of host genes on parasite adaptation. In this comprehensive review, we analyze the host genetic factors that influence parasite adaptation, including hormones, nitric oxide, immune cells, cytokine gene polymorphisms, parasite-specific receptors, and metabolites. We also establish an interactive network to better illustrate the complex relationship between host genetic factors and parasite-host adaptation. Additionally, we discuss future directions and collaborative research priorities in the parasite-host adaptation field, including investigating the impact of host genes on the microbiome, developing more sophisticated models, identifying and characterizing parasite-specific receptors, utilizing patient-derived sera as diagnostic and therapeutic tools, and developing novel treatments and management strategies targeting specific host genetic factors. This review highlights the need for a comprehensive and systematic approach to investigating the underlying mechanisms of parasite-host adaptation, which requires interdisciplinary collaborations among biologists, geneticists, immunologists, and clinicians. By deepening our understanding of the complex interactions between host genetics and parasite adaptation, we can develop more effective and targeted interventions to prevent and treat parasitic diseases. Overall, this review provides a valuable resource for researchers and clinicians working in the parasitology field and offers insights into the future directions of this critical research area.